Development of the FRS in Mexico: concerning converge to IFRS Formulation des NIF au Méxique: référent de convergence à NIIF - Fuentes Gómez, Helda María; Castiblanco Pinto, Yudy Yamile; Ramírez, Maricela (Cuadernos de Administración, 2011)
This article develops a conjunctural moment of the accounting profession worldwide, due to International Financial Reporting Standards (IFRS) have become very important since its creation, “as universally recognized accounting standards by companies, allowing each again compare the financial information between entities in the same sector, although the basis of their business is in different countries”, “stands Alberto del Castillo audit partner of PricewaterhouseCoopers.” The result of the application of these standards will allow the investment decisions are expedited and the markets move quickly, allowing a greater volume of transactions. (Pérez, 2009). Facing this reality, Colombia through Law 1314 of 2009, from 1 January 2010, begins the process of convergence to IFRS by delegating to the Technical Board of Public Accountancy (CTCP) and entity normalizer. Thus, for the accounting profession in Colombia is convenient to take a look at countries that have developed similar processes, such as the Mexican case. Since Mexico began this process since 2002 building its accounting regulatory body called FRS (Financial Reporting Standards in Mexico) without losing sight of the IFRS (International Financial Reporting Standards) issued by the IASB (International Accounting Standards Board of Accounting).